Reestablishment of the Brown Dog Tick Rhipicephalus sanguineus (s.l.) in Chișinău, Moldova: A Case of Indoor Infestation - Morozov Alexandr; Victorova Anna; Railean Nadejda; Toderas Ion (Veterinary Medicine and Science, 2025)
ABSTRACT The brown dog tick (Rhipicephalus sanguineus sensu lato) is the most widespread tick in the world and a well‐recognized vector of numerous pathogens affecting dogs and occasionally humans. This tick is highly adapted to living in human dwellings and can remain active year‐round even in some temperate regions. Due to its ability to reproduce indoors, R. sanguineus (s.l.) can establish populations in homes and kennels, leading to persistent infestations. In Moldova, however, R. sanguineus (s.l.) has been very rarely reported; since 1970, it was documented only once.